Policy enactment and educational quasimarkets: Analysing school offer and demand dynamics in Chile - Verger, Antoni; Bonal, Xavier; Zancajo, Adrián (Education Policy Analysis Archives, 2016)
This article challenges the main assumptions of public choice theory in education by analyzing the functioning of market mechanisms and the educational offer and demand dynamics in Chile - the country that has adopted quasimarket policies in education for a longer period and at a larger scale. In analytical terms, the article relies on the work on school choice and education markets developed by Stephen Ball, as well as on the conceptual framework developed by the same author most recently to understand the logics of action of schools in local educational spaces and the 'enactment' of education policy.